1982
DOI: 10.1111/j.1365-2621.1982.tb12914.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Gelation Properties of Actomyosin and Surimi Prepared from Atlantic Croaker

Abstract: Comminuted mixtures of fish muscle (surimi) and salt undergo a sol-gel transformation when subjected to heat processing which is responsible for the textural characteristics of fabricated imitation shellfish meats. Upon "setting" a fish muscle sol at temperatures below those conventionally used for heat processing meat products, a fine translucent gel network is formed which imparts strength and resiliency to the subsequently cooked gel product. Increased fiimness and opacity, as well as some loss in cohesiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…2). Furthermore, Lanier et al (1982) have indicated that an alkaline proteinase could reduce gel integrity at 60°C. This may be important, because our products were cooked to 64.4"C and were at 60°C about lo-15 min.…”
Section: Tspp: Is = 'R[and4andanda)2 + (Ym~andand)~]mentioning
confidence: 99%
“…2). Furthermore, Lanier et al (1982) have indicated that an alkaline proteinase could reduce gel integrity at 60°C. This may be important, because our products were cooked to 64.4"C and were at 60°C about lo-15 min.…”
Section: Tspp: Is = 'R[and4andanda)2 + (Ym~andand)~]mentioning
confidence: 99%
“…Fish muscle proteins differ in their critical gelling temperatures compared with proteins of egg white, whey, pork or beef muscle and chicken or turkey muscle (Lanier, Lin, Liu, & Hamann, 1982;Montejano, Hamann, & Lanier, 1984). Stronger gels can be obtained by preheating minced fish paste from Alaska pollock, Atlantic croaker, Bighead carp, Sardine or round herring at a temperature near 40 1C for a short time or by refrigeration overnight prior to further heating (Barrera, Ramirez, GonzalezCabriales, & Vazquez, 2002;Luo, Pan, & Ji, 2004;Morales, Ramirez, Vivanco, & Vazquez, 2001;Roussel & Cheftel, 1990;Ueda, Shimizu, & Simida, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Sano et al24) reported that the first development of gel elasticity of carp myosin was attributable mainly to the tail portion at a lower temperature. Lanier et al 25) also suggested that setting allowed "ordering" of the protein molecules, primarily through myosin tail portions. Although TGase mediated cross-linking is essentially responsible to walleye pollack surimi for the set gel formability, experimental results on the incorporation of MDC (Fig.…”
mentioning
confidence: 99%